Does Physician Retirement Affect Patients? A Systematic Review. Issue 3 (24th October 2019) - Lam, Kenneth; Arnold, Cameron G.; Savage, Rachel D.; Stall, Nathan M.; Zhu, Lynn; Wu, Wei; Piggott, Katrina; Bronskill, Susan E.; Rochon, Paula A.
Abstract : OBJECTIVES: Older patients that have aged with their doctors will likely experience their physician retiring. It is unclear if this interruption in continuity of care leaves patients at risk for adverse events or whether a new physician improves care. We sought to identify and synthesize findings from all articles examining the association between physician retirement and patient outcomes. DESIGN: Systematic review. We searched English‐language articles cataloged in Medline, Embase, Cochrane, and PsycINFO, from database inception to May 4, 2018. PARTICIPANTS: Any patient whose physician (generalist or specialist) retired. INTERVENTION: Physician retirement, defined as voluntary practice closure, death, or departure. MEASUREMENTS: Articles were categorized as anecdotes, qualitative studies, or quantitative studies. Each patient outcome was indexed under one of 11 themes (eg, adverse event, difficulty accessing care) and classified as favorable, neutral, or unfavorable. Patient outcomes included but were not limited to clinical (eg, death), resource utilization (eg, hospitalization), treatment plan adherence (eg, access to medications), and patient satisfaction (eg, expressed frustration). Two reviewers independently assessed study quality. RESULTS: Of 2099 articles screened, 17 met inclusion criteria: 12 anecdotes, 2 qualitative studies, and 3 quantitative studies. Most patient outcomes described were unfavorable. These included feelings of loss, difficulties with transition to a new provider, adverse clinical outcomes, and increased use of high‐cost services. The quality of qualitative studies was high, but that of quantitative studies was poor or moderate. CONCLUSION: Current evidence from qualitative studies suggests physician retirement affects patients unfavorably and that patients are vulnerable during this transition of care. High‐quality quantitative research is lacking to identify whether this disproportionately affects older adults and whether physician retirement has significant consequences for the broader healthcare system. J Am Geriatr Soc 68:641–649, 2020